Fancy Nancy : explorer extraordinaire! - O'Connor, Jane.; Preiss-Glasser, Robin (New York : HarperCollinsPublishers, 2009)
Nancy and her friend Bree explore the fascinating world of birds and insects in their exclusive and glamorous Explorers Extraordinaire Club.
"Everything in this book is scientifically accurate. (That's a fancy way of saying it's all true)--t.p.
Keywords: Clubs -- Fiction; Insects -- Fiction; Birds -- Fiction; Vocabulary -- Fiction